2018
DOI: 10.1021/acs.bioconjchem.7b00781
|View full text |Cite
|
Sign up to set email alerts
|

Human Telomeric G-Quadruplex Selective Fluoro-Isoquinolines Induce Apoptosis in Cancer Cells

Abstract: Small molecules that stabilize G-quadruplex structures in telomeres can prevent telomerase enzyme mediated telomere lengthening and subsequently lead to cell death. We herein report two fluoro-isoquinoline derivatives IQ1 and IQ2 as selective ligands for human telomeric G-quadruplex DNA. IQ1 and IQ2 containing different triazolyl side chains have been synthesized by Cu (I) catalyzed azide-alkyne cycloaddition. Fluorescence Resonance Energy Transfer (FRET) melting assay and fluorescence binding titrations indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 94 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…G-quadruplexes were observed for the first time in the early 1900s and they were characterized by x-ray diffraction in the sixties [2]. Nowadays, applications based on G-quadruplex are many and diverse, ranging from diagnostic tools, biosensing and medicine [3][4][5]. In addition G-quadruplex structures have been visualized in human cells [6], being present at the end of the chromosomes (telomeres) as well as in some regions of the genome like 5 -UTR regions and oncogene promoters (e.g., c-kit, bcl-2 and c-myc), emerging as attractive targets for cancer therapy [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…G-quadruplexes were observed for the first time in the early 1900s and they were characterized by x-ray diffraction in the sixties [2]. Nowadays, applications based on G-quadruplex are many and diverse, ranging from diagnostic tools, biosensing and medicine [3][4][5]. In addition G-quadruplex structures have been visualized in human cells [6], being present at the end of the chromosomes (telomeres) as well as in some regions of the genome like 5 -UTR regions and oncogene promoters (e.g., c-kit, bcl-2 and c-myc), emerging as attractive targets for cancer therapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, cancer cells have long telomeres providing uncontrolled cellular proliferation [7,8]. Therefore, appropriately designed G-quadruplex ligands have played a crucial role in recognizing such structures, promoting telomere damage and therefore favoring cell death [3].…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of azacyanines with tel24 were first investigated using UV-Vis and circular dichroism (CD) spectroscopy in order to quickly survey and confirm the presence of interactions between the azacyanines and tel24. Such a survey also reveals changes in the secondary structure of tel24 upon azacyanine binding and the effect of azacyanine structure on tel24 binding [25,[28][29][30][31][32][33][34][35][36][37]. Our previous structural studies using NMR have shown that one azamethyl was binding to one tel24 G-quadruplex structure between the top quartet and the A-T base pairing in the loop region.…”
Section: Determination Of Binding Using Uv-vis and CD Spectroscopymentioning
confidence: 92%
“…Several studies investigating the effect of the benzimidazole scaffold on telomeric DNA and oncogene promoters such as KRAS and VEGFR that are known to fold into quadruplex structures were recently reported [24][25][26][27][28][29][30]. In addition, several reports investigating the effect of such small molecules on different cancer lines and promoting G-quadruplexes as plausible targets in cancer therapy were also published [31][32][33][34][35][36]. Based on all these reported studies and our knowledge on azamethyl, we were inspired to explore a series of azacyanine compounds as potential G-quadruplex stabilizing compounds with the hope of finding a better candidate than azamethyl and understanding the effect of molecular structure on molecular recognition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the structural and topological diversity of quadruplexes and ligand-binding specificity remain key challenges in developing effective and selective G4 DNA-binding ligands [12]. A considerable number of small ligands have been developed as potential G4 binders, including Telomestatin ® , porphyrinoids, quinolones, alkaloids, carbazoles, acridine derivatives [13,14,15,16,17,18,19,20,21,22,23,24,25,26], and recently, reductive-activated G4-binders [27]. Besides ligands that have a planar surface for interaction with G4 DNA, molecules containing bi-aryl linkages have also emerged recently as promising candidates [28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%